Beta-lactam antibiotics use in intensive care units - the pathophysiological, pharmacokinetic, pharmacodynamic and pharmacoeconomic approach - Perić Aneta; Šurbatović Maja; Vezmar-Kovačević Sandra; Antunović Mirjana; Veljović Milić; Krstić-Lečić Ivana; Đorđević Dragan; Kilibarda Vesna; Zeba Snježana; Dobrić Silva (Vojnosanitetski Pregled)
nema